Antimicrobial Effectiveness in Number of Fungal in Artificial Diet of Silkworm and the Quality of Cocoon - Jamila, .; Syamsu, Jasmal A; Syatrawati, . (Universitas Hasanuddin, 2014)
Research was carried out to investigate the effectiveness of antibacterial agents on both fungal count and on quality of silkworm cocoon. Two strain of silkworm (Bombyx mori) i.e. Perhutani and China strain were used in this study. The silkworms were feed on artificial diet containing either salt, calcium propionate, or potassium sorbate with level 2 gram/100 gram feed dry matter. The result indicated that use of different agent as antimicrobial significantly inhibited the growth of fungal. Salt was the best inhibitory agent compared to calcium propionate and potassium sorbat when adding to the diet, While silkworm Perhutani performed better than China strain when feed on such diet.